2018
DOI: 10.1039/c7nr07614b
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembled thermoresponsive nanostructures of hyaluronic acid conjugates for osteoarthritis therapy

Abstract: Under pathological conditions, joints and skin are often affected by an imbalance in the breakdown and production of hyaluronic acid (HA). The unique biochemical and biomechanical properties provided by HA must be restored for the long-term lubrication and cushioning effects. To overcome the inconvenience of repeated injections and the rapid degradation of exogenous HA treatments, HA is conjugated to a thermosensitive polymer, enabling the spontaneous formation of nanoparticles (HA Nano) at body temperature. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
85
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 24 publications
0
85
0
Order By: Relevance
“…Another promising type of drug delivery system, which can be formulated with HA and its derivatives of synthesis, is represented by nanoparticles. Hyaluronan can be a constituent element of nanoparticles [192,193], but can also be used to cover nanoparticles, in order to improve the targeting efficiency and the therapeutic action of the encapsulated drugs [194]. HA-nanoparticles are being investigated for a number of administration routes and customized applications: for example, HA-Flt1 peptide conjugate nanoparticles might represent a next-generation pulmonary delivery carrier for dexamethasone in the management of asthma [193], while chitosan nanoparticles coated with HA and containing betamethasone valerate have displayed a great potential for the topical treatment of atopic dermatitis [194].…”
Section: Applications Of Ha and Its Derivativesmentioning
confidence: 99%
“…Another promising type of drug delivery system, which can be formulated with HA and its derivatives of synthesis, is represented by nanoparticles. Hyaluronan can be a constituent element of nanoparticles [192,193], but can also be used to cover nanoparticles, in order to improve the targeting efficiency and the therapeutic action of the encapsulated drugs [194]. HA-nanoparticles are being investigated for a number of administration routes and customized applications: for example, HA-Flt1 peptide conjugate nanoparticles might represent a next-generation pulmonary delivery carrier for dexamethasone in the management of asthma [193], while chitosan nanoparticles coated with HA and containing betamethasone valerate have displayed a great potential for the topical treatment of atopic dermatitis [194].…”
Section: Applications Of Ha and Its Derivativesmentioning
confidence: 99%
“…In order to enhance the cartilage-targeting delivery efficiency and minimize dosage requirements, construction of carriers with good safety, precise cartilage-targeting and high delivery efficiency is essential. A number of delivery vectors for miRs have been reported, such as adenoviruses, collagen scaffolds and hydrogels [30,31], and biochemical modifications that can selectively bind to cartilage or play specific biological functions may further improve the vectors. For example, Li et al reported that N-Cadherin peptidomimetic modified self-assembling polypeptide nanomaterials enhances the chondrogenic differentiation of mesenchymal stem cells (MSCs) [32].…”
Section: Discussionmentioning
confidence: 99%
“…The preparation of nanoparticles was performed as described previously [11]. We followed and modified the methods of Maudens et al [12]. 1,2-Dilauroyl-sn-glycero-3-phosphoethanolamine (DLPE) and 1,2-dilauroyl-sn-glycero-3glycerol (DLPG) were from Avanti Polar Lipids Inc. (Alabaster, AL, USA).…”
Section: Methodsmentioning
confidence: 99%